Raja Rammohun Roy Library Foundation and its Role in Galvanizing the Public Library Movemnet in India - Deshpande, K. S.; Hungund, B. B. (Journal of Information and Knowledge, 2001)
Raja Rammohun Roy Library Foundation (RRRLF). was established by the Government of India in 1972 to activate the public library movement in the Country. It has been funding the public libraries in various States. But much is left unattended; like instigating the States where there are no library legislation to introduce them early to initiate dialogues and discussions through seminars to strengthen the existing library laws by introducing amendments, to review and critically evaluate the work done by the beneficiares of the Fund at regular intervals. The paper recommends a study of IFLA standards in the light of recent developments, for adoption in public libraries. It also recommends RRRLF to publish documents relevant to the puplic library scenarios in the country and to undertake surveys on personal libraries and reading habits. The authors desire that the RRRLF transforms, metamorphoses India into a land of libraries.